Increase in Expression of α1 and α2/δ1 Subunits of L-Type High Voltage-Gated Calcium Channels After Sustained Ethanol Exposure in Cerebral Cortical Neurons - Masashi Katsura; Masahiro Shibasaki; Shinsuke Hayashida; Fumiko Torigoe; Atsushi Tsujimura; Seitaro Ohkuma (Elsevier, 2006)
Previous reports revealed up-regulation of L-type high voltage-gated calcium channels (HVCCs) in mouse brains with ethanol physical dependence. We investigated mechanisms of enhancement of L-type HVCC function using mouse cerebrocortical neurons exposed to 50 mM ethanol for 3 days and the brains of mouse physically dependent on ethanol. Ethanol facilitated 30 mM KCl-stimulated 45Ca2+ influx in dose- and duration-dependent manners, which was abolished by nifedipine, an inhibitor specific to L-type HVCCs, but not by inhibitors for other types of HVCCs. Increase in [3H]PN200-110 binding to the particulate fractions from the ethanol-treated neurons was due to increased Bmax value with no changes in Kd value. Western blot analysis showed the increased expression of α1C, α1D, and α2/δ1 subunits with decreased β4 subunit expression and no changes in expressions of α1A, α1B, α1F, and α2 subunits. A similar pattern of the changes in the expression of these subunits of L-type HVCCs were observed in the cerebral cortex from mouse with ethanol physical dependence. These results indicate that sustained ethanol exposure to the neurons induces up-regulation of L-type HVCCs, which is due to increased expressions of α1C, α1D, and α2/δ1 subunits, and produces no alterations in P/Q- and N-type HVCC functions. Keywords:: ethanol (alcohol) physical dependence, high voltage-gated calcium channel, Ca2+ influx, [3H]PN200-110 binding, cerebral cortical neuron